Near Ground Target Signal Localization At 433 MHz Using Improved Trilateration Method - Zaniani, Marjan Moradi (2012)
Localizing near ground target with Trilateration method implies the positioning of target coordinate towards a known base point with measuring distance from target to no less than three recognized reference points. Distance measurement between three sides of Trilateration could be performed with different measurement techniques such as RSS or TOA. RSS measurement technique was used by this research to investigate the Trilateration concept for determining location on low level antenna (approximately 1 to 3 m height above ground) at 433 MHz. Initially distance measurement model versus losses relating to antenna height was measured.